2012
DOI: 10.1016/j.nicl.2012.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility-weighted imaging at 7T: Improved diagnosis of cerebral cavernous malformations and associated developmental venous anomalies

Abstract: Background and aimIn the diagnosis of cerebral cavernous malformations (CCMs) magnetic resonance imaging is established as the gold standard. Conventional MRI techniques have their drawbacks in the diagnosis of CCMs and associated venous malformations (DVAs). The aim of our study was to evaluate susceptibility weighted imaging SWI for the detection of CCM and associated DVAs at 7 T in comparison with 3 T.Patients and methods24 patients (14 female, 10 male; median age: 38.3 y (21.1 y–69.1 y) were included in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Our findings may be of value in numerous MRI applications including T2*, 70,71 proton‐density, 72 susceptibility‐weighted imaging (SWI) 73 and quantitative susceptibility mapping, 74 as our method paves the way to increases in spatial and temporal resolution under conditions compatible with clinical time constraints. Although our application focuses on T2* imaging, the SPARKLING trajectories may be used for other contrast such as T2 or T1 or for dynamic imaging, by adapting the acquisition parameters.…”
Section: Discussionmentioning
confidence: 89%
“…Our findings may be of value in numerous MRI applications including T2*, 70,71 proton‐density, 72 susceptibility‐weighted imaging (SWI) 73 and quantitative susceptibility mapping, 74 as our method paves the way to increases in spatial and temporal resolution under conditions compatible with clinical time constraints. Although our application focuses on T2* imaging, the SPARKLING trajectories may be used for other contrast such as T2 or T1 or for dynamic imaging, by adapting the acquisition parameters.…”
Section: Discussionmentioning
confidence: 89%
“…SWI shows a high sensitivity for pathologies that cause magnetic field inhomogeneity such as deoxygenated blood, hemosiderin, ferritin, and calcium . SWI is useful for the detection of both cavernous malformations and DVAs; the sensitivity increases with increased magnetic field strength (ie, 3 T vs. 1.5 T) …”
Section: Neuroimaging Findings: Advanced Mri and Petmentioning
confidence: 99%
“…9), 53 and low-flow VMs, including CCM, 20,23,88 brain capillary telangiectasia, 28 or Sturge-Weber syndrome. 48,110 Most importantly, the findings from SWI, especially at ultrahigh fields (that is, 7 T), 29 are shown to correlate with histopathological studies. 88 SWI is a promising technique since its findings correlate well with "gold-standard" techniques for detecting VMs, including digital subtraction angiography and time-of-flight MRA.…”
Section: Monitoring Outcome In Strokementioning
confidence: 92%
“…Various studies have demonstrated the effectiveness of SWI in outcome prediction using SWI for hemorrhage grading, 51 the dichotomization of patients with and those without CMBs, 29,33 or the detection of a greater number and volume of lesions. 5,9,94,95,99 Despite having various SWI methods for outcome prediction, the current state of research has yet to reveal which method would exhibit the highest accuracy and specificity in predicting outcome and recovery.…”
Section: 82 Outcome Predictionmentioning
confidence: 99%